PKM PENERAPAN MEDIA SOSIAL DALAM KREATIVITAS MAHASISWA PADA MATA KULIAH BAKERY - Simanjuntak, Jeannete Claudia Stefany; Ramadhani Pasi, Anggie; Tresno Ingtyas, Fatma; Sabrina, Elsa (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study is to analyze the influence of social media on student creativity in Bakery courses. This research uses a qualitative analysis method, namely using the literature with the type of meta-analysis research, which summarizes, summarizes, and reviews as many as 15 journals in SINTA. The samples of this study were students who were taking Bakery courses and students who had studied Bakery courses. The results of this study indicate that the influence of social media on student creativity in Bakery courses has positive and negative impacts. The positive impact that can be obtained because it is an effective means to increase student creativity in making Bakery products so that they can open their own Bakery shop entrepreneurship. While the negative impact is dependence on social media content and plagiarism. For this reason, the role of social media for students must be adjusted to its use.